Examining Pathways Underlying the Association Between Maternal Depressive Symptoms and Infant Weight Outcomes. (29th May 2020) - Thompson, Amanda; Wasser, Heather; Nulty, Alison; Bentley, Peggy
Abstract: Objectives: Evidence for an association between maternal depression and child obesity is mixed. We test the association between maternal depressive symptoms (DS) and infant weight-for-age z-scores (WAZ) and three pathways, limited breastfeeding, maternal responsivity, and infant temperament, proposed to underlie this association. Methods: Data come from 371 African-American mother-infant pairs participating in the Mothers & Others Study, a home-based intervention to prevent early development of obesity. Data were collected at 28-weeks gestation and 3, 6, 9, 12, and 15 months postpartum. At each postnatal visit, infant weight was directly measured and maternal DS, breastfeeding history, infant feeding styles, and infant temperament were collected using validated instruments. Longitudinal mixed effects models tested the association between maternal DS and infant WAZ. Path analyses tested for mediation by breastfeeding duration, responsive feeding, and infant fussiness. DS were included in final models as a 4-level categorical variable (no symptoms, prenatal only, postnatal only, both pre- and postnatal) to test whether the timing and/or duration of maternal DS were differently associated with WAZ. Results: Prevalence of maternal DS ranged from 30.4% prenatally to 13.9% at 15 months. Maternal DS were inversely associated with infant WAZ in adjusted models. A significant time trend was found, with infants of depressed mothers having lower WAZ trajectories. No evidence for mediation through breastfeeding or responsive feeding was found. Maternal DS had a significant indirect effect through perception of infant fussiness (β = 0.02, CI: 0.01, 0.04). Finally, compared to infants of mothers with no depressive symptoms, infants of mothers with both pre- and postnatal symptoms had significantly smaller WAZ from 0–15 months (β = −0.41, P  = 0.03). Conclusions: Our analysis suggests that maternal DS are associated with lower, not higher, infant WAZ. Maternal perception of infant temperament may be an important underlying pathway, but more research is needed on the mechanisms linking maternal depression to caregiving practices and infant weight gain trajectories. Funding Sources: National Institute of Child Health and Human Development.